Design, characterization and in vitro evaluation of antifungal polymeric films - Real, Daniel Andres (2013)
The objective of the present paper was the development and the full characterization of antifungal films. Econazole nitrate (ECN) was loaded in a polymeric matrix formed by chitosan (CH) and carbopol 971NF (CB). Polyethylene glycol 400 and sorbitol were used as plasticizing agents. The mechanical properties of films were poorer when the drug was loaded, probably because crystals of ENC produces network outages and therefore reduces the polymeric interactions between the polymers. Polymers–ECN and CH–CB interactions were analyzed by Fourier-transform infrared spectroscopy (FTIR), thermal gravimetry analysis, and differential thermal analysis (DTA-TGA). ECN did not show structure alterations when loaded into the films. In scanning electron microphotographs and atomic force microscopy analysis, films prepared with CB showed an evident wrinkle pattern probably due to the strong interactions between the polymers, which were observed by FTIR and DTA-TGA. The in vitro activity of the formulations against Candida krusei and Candida parapsilosis was twice as greater as the commercial cream, probably as a result of the antifungal combination of the drug with the CH activity. All these results suggest that these polymeric films containing ECN are potential candidates in view of alternatives dosages forms for the treatment of the yeast assayed.